Lipid Components in the Dynamin Fraction Prepared from Rat Brain - Satoko Ueno; Keiji Seno; Yoko Maruyama; Fumio Hayashi; Hiroshi Miyoshi; Mitsuhiro Morita; Shohei Maekawa (International Journal of Lipids, 2018)
Membrane dynamics in the presynaptic region of the neuron is a key process of neuronal signal transduction. Dynamin plays a central part during endocytosis participating in the deformation of membrane structure and constriction. During the study of molecular interaction of presynaptic proteins, we found that dynamin fraction prepared from brain extract contains several lipid components. Fractionation of lipids with thin layer chromatography and mass-analysis showed the presence of phosphatidylcholine, phosphatidylethanolamine, cerebroside, cholesterol and its-derivatives, and triacylglycerol. Since the GTPase activity of bacterially expressed dynamin was activated by the extracted lipid fraction, lipid components that affect the GTPase activity of dynamin was screened and cerebroside, hydroxycholesterols, cholesterol, and triacylglycerol were found to activate the GTPase activity. This result not only suggests the possibility that several neutral lipids participate in the membrane dynamics, but also revealed the possibility that a protein fraction contains lipid components even if its purity was confirmed with SDS-PAGE.
Keywords: brain